Experimental Investigation of Polyurea-Coated Steel Plates at Underwater Explosive Loading - Li-hui Dai; Cheng Wu; Feng-jiang An; Sha-sha Liao (Advances in Materials Science and Engineering)
To improve the survivability of ship structures at underwater explosion, thin steel plates coated with polyurea were used to investigate the blast protection effect. During the experimental tests of bare steel plates at different standoff, an appropriate distance was selected as the reference standoff to perform the tests of coated plates. Experimental tests of different coating locations (front versus back) and coating thickness were carried out to study the influencing factors of blast resistance for metal substrate plates. Compared with the bare steel plates, the polyurea coating was found to reduce the deformation of the test plates at blast tests in both cases of the front and back surface locations of the polyurea layer. An increase in the coating thickness also mitigates substantially the deformation of plates. In addition, the properties of the material and the substrate-coating bond strength may also affect the protective effect of the polyurea coating.